2022
DOI: 10.1002/cncy.22604
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Milan System for Reporting Salivary Gland Cytopathology: A systematic review and meta‐analysis

Abstract: BACKGROUND:The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) is a standard, evidence-based classification system for salivary gland fine-needle aspiration (SG-FNA). Since it was published in 2018, many researchers across the world have applied this uniform reporting system to their cohorts. METHODS: The authors comprehensively reviewed cohort studies conducted since publication of the MSRSGC and performed a meta-analysis. The risk of neoplasm and the risk of malignancy (ROM) were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first systematic review and meta-analysis regarding the use of the IAC Yokohama system for reporting breast FNAs. Similar works have been published about other cytopathology reporting systems, such as the Bethesda System for Reporting Thyroid Cytopathology, 33 the Milan System for Reporting Salivary Gland Cytopathology, 34 the Paris System for Reporting Urinary Cytopathology, 35 and the Papanicolaou System for Reporting Pancreatobiliary Cytopathology. 36 First, we calculated the pooled ROM of each reporting category, using the extracted data from 18 studies published between 2019 and 2021.…”
Section: Discussionmentioning
confidence: 72%
“…To our knowledge, this is the first systematic review and meta-analysis regarding the use of the IAC Yokohama system for reporting breast FNAs. Similar works have been published about other cytopathology reporting systems, such as the Bethesda System for Reporting Thyroid Cytopathology, 33 the Milan System for Reporting Salivary Gland Cytopathology, 34 the Paris System for Reporting Urinary Cytopathology, 35 and the Papanicolaou System for Reporting Pancreatobiliary Cytopathology. 36 First, we calculated the pooled ROM of each reporting category, using the extracted data from 18 studies published between 2019 and 2021.…”
Section: Discussionmentioning
confidence: 72%
“…Subsequent reports verified its value in the preoperative evaluation of salivary lesions. 2,5 However, ND category, defined as the aspirate provides insufficient diagnostic material to provide an informative interpretation due to qualitative and/or quantitative reasons, is one of the factors that handicaps the diagnostic efficacy of FNAC for salivary lesions. This may result from rare or absent cells less than 60 lesional cells, poorly prepared slides with artifacts (e.g., air-drying, obscuring blood, and poor staining) that preclude the evaluation of the cellular component, non-neoplastic (normal) salivary gland elements in the setting of a clinically or radiologically defined mass.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has been reported that the FNAC of the salivary glands is highly specific for the detection of neoplasia (up to 98%) and malignancy (up to 96%). 2 However, it is less sensitive for the detection of neoplasia (up to 96%) and malignancy (up to 79%). 2 The primary purpose of salivary FNAC is to assess the nature of the lesions, namely nonneoplastic versus neoplastic and benign versus malignant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations